A low-carbon alkali activated slag based ultra-high performance concrete (UHPC): Reaction kinetics and microstructure development. (20th August 2022) - Zhang, X.Y.; Yu, R.; Zhang, J.J.; Shui, Z.H.
Abstract: Ultra high performance concrete (UHPC) is a cement-based material with great development prospects. However, the production of cement will produce a large amount of CO2, which does not conform to the current global trend of energy conservation and emission reduction, and limits the further development of UHPC. One of the ways to further develop UHPC is to reduce the carbon emissions in the production process of UHPC. The aim of this study is to develop a low-carbon alkali activated slag based Ultra-High Performance Concrete (A-UHPC) with ultra-low moisture content. Firstly, based on the particle dense packing model, an optimized combination of low-carbon cementitious mixture and aggregates skeleton is designed. Then, the effects of moisture content on the macro-properties, hydration mechanism and micro-mechanism of the developed A-UHPC are studied. The experimental results show that the fresh performance and macroscopic mechanical properties of A-UHPC are advanced at low moisture content. When the water-binder ratio is 0.29, the compressive strength at 28 d is the highest, reaching 118 MPa. Besides, low moisture content A-UHPC also shows good microscopic properties: its hydration degree can reach 62.58% and the longest molecular chain length of the polymer is about 4.74. In general, the developed A-UHPC can meet the requirement of high performance and low CO2 emission simultaneously, which could be one of the most suitable choices to achieve the goal of "Carbon peak and Carbon neutral" in the near future. Highlights: A novel method for designing a low carbon UHPC is presented. The newly developed UHPC exhibits admirable ecological value. Mineral powder and alkali-activator are adopted in UHPC. Low moisture content A-UHPC is developed. 5.The effect of water on the macro and micro properties of A-UHPC is studied.